2010
DOI: 10.1007/s11606-010-1576-6
|View full text |Cite
|
Sign up to set email alerts
|

When Should Patient Intuition be Taken Seriously?

Abstract: As a style of information processing, intuition involves implicit perceptual and cognitive processes that can be quickly and automatically executed without conscious mental will, such that people know more than they can describe. Patient intuition can influence patient and clinician decision-making and behavior. However, physicians may not always see patient intuition as credible or important, and its management in the clinical setting is poorly understood. This paper takes a step toward suggesting conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 42 publications
2
21
0
1
Order By: Relevance
“…Moreover, patients reported to use rational processes, intuitive processes or a combination as is in line with current viewpoints about medical decision‐making (Buetow & Mintoft, ; Bate, Hutchinson, Underhill, & Maskrey, ; Ubel, ). Therefore, both rational and intuitive processes should be facilitated by the PtDA (De Vries, Fagerlin, Witteman, & Scherer, ).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, patients reported to use rational processes, intuitive processes or a combination as is in line with current viewpoints about medical decision‐making (Buetow & Mintoft, ; Bate, Hutchinson, Underhill, & Maskrey, ; Ubel, ). Therefore, both rational and intuitive processes should be facilitated by the PtDA (De Vries, Fagerlin, Witteman, & Scherer, ).…”
Section: Discussionsupporting
confidence: 75%
“…HPs perceived their role in the decision‐making process was mainly to provide the patient with evidence‐based medical information. Previous studies have shown that rationally based health decisions are viewed as more viable and credible by HPs than intuitive‐based decisions; for these are thought to be more bias prone (Buetow & Mintoft, ). Therefore, some HPs claim to base their health decisions on rational deductions and are reluctant to take patients' intuition into account (Buetow & Mintoft, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many kinds of evidence may have relevance to clinical decision making. Buetow and Kenealy (2000) and Buetow and Mintoft (2011) argue that EBM too severely limits the use of nonscientific knowledge, including patient intuition, that may complement, and enhance EBP decision making.…”
Section: Using Evidence In Evaluations Of the Performance Of Professimentioning
confidence: 99%
“…Although a full examination of the book is beyond the scope of this review, I do wish to comment on key issues raised in chapter 6. As a public critic of EBM who has also suggested conditions under which clinicians should take patient intuition seriously [3], I agree that intuition is an inherent and valuable part of the process of clinical judgement, linking tacit with explicit understanding in order to reintegrate the modern scientific method and concern for the whole person. I also recognize the irony in EBM seeing intuition as flawed, yet deriving some of its own popularity 'from the intuitively obvious nature of its name' [4].…”
mentioning
confidence: 97%